Evidence Based Global Health Manual for Preterm Birth Risk Assessment - Anumba, Dilly OC; Jayasooriya, Shamanthi M. (Springer Nature, 2022)
This is an open access book. In this open access book the NIHR Global Health research group on preterm birth, PRIME, prioritizes the development of prenatal risk assessment guidance for preterm birth. This book is based on global literature, published international, national and regional guidance and it is structured into six chapters providing: an overview of the domains for risk assessment and the summary recommendations in greater depth maternal demographics and past pregnancy histories, accurate pregnancy dating, and the contribution of infection, nutritional status and substance misuse to preterm birth risk. Each chapter has structured sections which include a) background information, b) an evidence statement highlighting the risk factors covered, and c) practical recommendations for evaluating those risks as well as the evidenced recommended and effective interventions for women deemed to be at risk. The chapter ends with clinical and research recommendations regarding factors of unknown or unproven risk ("myth busters"). This open access book will be a very useful guide for all health care professionals involved in delivering pregnancy care.